Combined exosome of adipose-derived mesenchymal stem cell and hyaluronic acid delays early osteoarthritis progression of ovine sheep model: Clinical, radiographic, macroscopic and microscopic evaluation [version 3; peer review: 2 approved, 1 not approved] - Marcel Prasetyo; Radiana Dhewayani Antarianto; Tri Isyani Tungga Dewi; Bambang Pontjo Priosoeryanto; Trevino Aristakus Pakasi; Angela Jennifer Tantry; Alida Harahap; Ismail Hadisoebroto Dilogo; Jessica Fiolin; Ludwig Andribert Powantia Pontoh (F1000Research)
Background Current treatment of osteoarthritis (OA) mainly focused on treating symptoms. Exosome from Adipose-derived Mesenchymal Stem Cell (Ad-MSC) have been shown to delay degenerative process. This study aimed to investigate the clinical, radiological and histological impact of combined intra-articular (IA) hyaluronic acid (HA) and exosome Ad-MSCs in-vivo using a larger animal model with low-grade OA. Methods Eighteen male Ovies aries sheep underwent total lateral meniscectomy and conventional radiography was performed to confirm low-grade OA after 6 weeks. The sheep were divided into three groups, Group 1 (G1; n=6) received thrice exosome injections, G2 (n=6) received twice HA injection, and G3 (n=6) received both treatments with a 1-week interval after 10 days of meniscectomy. Clinical evaluations were conducted using the Clinical Lameness Score (CLS), radiographic with X-ray using OA score by Innes et al, while macroscopic evaluation by Osteoarthritis Research Society International (OARSI) scores. Results Lameness parameter scored lowest in G3 significantly (2.0±0.0 VS 2.7±0.52 VS 2.7±0.52; p=0.024) at the second month although the overall CLS score did not significantly differ at the 3rd month. The best improvement of conventional total OA radiographic score at the 3rd month compared to all groups (5.2±1.17 vs 6.3±0.82 vs 6.7±1.03; p=0.053). Macroscopic OARSI evaluation showed no difference (p=0.711). Conclusions Combined repeated exosome Ad-MSC and HA IA injection proven to delay OA progression, however longer duration of follow up is required to evaluate its long-term effect.